2013
DOI: 10.1042/bj20121713
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Trit1 is a tRNA[Ser]Sec-isopentenyl transferase required for full selenoprotein expression

Abstract: Selenoproteins are proteins carrying the rare amino acid Sec (selenocysteine). Full expression of selenoproteins requires modification of tRNA([Ser]Sec), including N(6)-isopentenylation of base A(37). We show that Trit1 is a dimethylallyl:tRNA([Ser]Sec) transferase. Knockdown of Trit1 reduces expression of selenoproteins. Incubation of in vitro transcribed tRNA[Ser]Sec with recombinant Trit1 transfers [(14)C]dimethylallyl pyrophosphate to tRNA([Ser]Sec). 37A>G tRNA([Ser]Sec) is resistant to isopentenylation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 32 publications
(41 reference statements)
0
38
0
Order By: Relevance
“…The ferroptosis-inducing compound FIN56 depletes CoQ 10 by modulating squalene synthase activity (SQS), which in part drives accumulation of lethal lipid peroxidation (Shimada et al, 2016b). Statin drugs, which inhibit HMG CoA reductase, the rate-limiting enzyme of the mevalonate pathway, sensitize cells to ferroptosis, presumably by depleting CoQ 10 , and possibly by also inhibiting downstream tRNA isopentenylation via TRIT1, which is required for the biosynthesis of GPX4 (Fradejas et al, 2013; Shimada et al, 2016b; Viswanathan et al, 2017). …”
Section: The Biochemical Control Of Ferroptosismentioning
confidence: 99%
“…The ferroptosis-inducing compound FIN56 depletes CoQ 10 by modulating squalene synthase activity (SQS), which in part drives accumulation of lethal lipid peroxidation (Shimada et al, 2016b). Statin drugs, which inhibit HMG CoA reductase, the rate-limiting enzyme of the mevalonate pathway, sensitize cells to ferroptosis, presumably by depleting CoQ 10 , and possibly by also inhibiting downstream tRNA isopentenylation via TRIT1, which is required for the biosynthesis of GPX4 (Fradejas et al, 2013; Shimada et al, 2016b; Viswanathan et al, 2017). …”
Section: The Biochemical Control Of Ferroptosismentioning
confidence: 99%
“…[Ser]Sec hypomodification and selenoprotein expression but did not examine other potential substrates, such as the tRNA Ser tRNAs identified here (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The tumorigenic potential of A549 cells in nude mice was reduced by ectopic expression of TRIT1 (20), and genetic linkage disequilibrium refined a region responsible for cancer progression on chromosome 1p34 that includes a TRIT1 rare mutation allele associated with poor survival in some ethnic groups (21). Human TRIT1 was confirmed to be an IPTase by complementation of a suppressor tRNA Ser UCA-mediated phenotype in mod5-deficient S. cerevisiae (20) and by a direct IPTase activity assay of recombinant TRIT1 protein (18).Selenocysteine tRNA (tRNA [Ser]Sec ) is the only tRNA known to contain i6A37 in mammals (22,23). Human TRIT1 has not been examined for its activity with native tRNA [Ser]Sec and other potential human tRNA substrates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Um34 methylation of tRNA [Ser]Sec requires aminoacylated tRNA [Ser]Sec , most likely with Sec [34]. Recently, it was shown that N6-isopentenylation of base A37 is catalyzed by Trit1, a dimethylallyl:tRNA [Ser]Sec -transferase [35]. …”
Section: Selenium In Biomoleculesmentioning
confidence: 99%